The Impact of Knowledge Creation and Sharing on Innovation - Atkočiūnienė, Zenona Ona Ona; Petronytė, Aurelija (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]After data analysis, it was concluded that knowledge management in an organization is an important factor that makes a positive contribution to the organization’s activities. Systematically organized knowledge management in an organization is ensured by the application of a knowledge management cycle, model or process. In order to gain a competitive advantage, it is important for the organization to carry out innovative activities, which is determined by consistent knowledge creation and sharing in the organization. It is important that the knowledge conversion model is closely linked to innovation. Systematic knowledge creation and sharing improves the development of new products in organizational projects, which increases the organization’s competitiveness. The results obtained using the empirical quantification method showed that knowledge creation and sharing have a positive effect on innovative behavior.
Keywords: knowledge management; knowledge management cycles; processes; models; knowledge creation; knowledge sharing; innovation